Experimental study on prevention and control of coal spontaneous combustion with heat control inhibitor. (November 2018) - Wu, Zhengyan; Hu, Shanshan; Jiang, Shuguang; He, Xinjian; Shao, Hao; Wang, Kai; Fan, Deqiang; Li, Wanrong
Abstract: Traditional inhibitors have such disadvantages as unstable inhibitory effects and short active lifetimes. Sodium bicarbonate, stable in nature, is expected to absorb heat and lower the temperature upon heated and decomposition, enabling its decomposition product to be effective for preventing coal oxidation and spontaneous combustion. Accordingly, the present study investigates the characteristics of sodium bicarbonate and proposes a novel method for preventing the spontaneous combustion of coal using sodium bicarbonate. By establishing a programmed temperature experimental system of coal spontaneous combustion in the laboratory, the researchers added sodium bicarbonate (0.5–3 g) to the coal samples, and analyzed changes in CO and O2 concentration. The results out of the present experimental conditions, compared with those of coal samples treated with magnesium and calcium chlorides, show that adding different amounts of sodium bicarbonate can inhibit coal oxidation with an optimal addition amount of 3 g. When the amount of sodium bicarbonate added was larger than 2 g and the temperature above 130 °C, its inhibitory effect is more significant than that of existing inhibiting agents. Graphical abstract: Image 1 Highlights: In this paper, heat control inhibitor is used to inhibit coal spontaneous combustion. The loss of water weakens the effect of the inhibitor. When the amount of sodium bicarbonate was more than 2 g, the inhibitory effect was already desirable.